Objects of Expert Knowledge: On Time and the Materialities of Conversion to Christianity in the Southern New Hebrides - Mitchell, Jean (Anthropologica, 2013)
In 1848 Presbyterian missionaries John and Charlotte Geddie travelled 20,000 miles to Aneityum, an island in the New Hebrides archipelago (now Vanuatu), in the southwest Pacific, where they established the first "successful" Christian mission in island Melanesia. Through evangelical desire, expert knowledge and ambitious projects, the Geddies along with converts, Samoan "teachers" and Scottish missionaries, trans formed everyday and ritual practices within a surprisingly short period. I draw attention to the materiality of conversion to argue that "becoming" Christian was connected to knowing and "doing things" evident in how objects made and remade the temporalities of the sacred and mundane. Such fraught material enactments made visible the divergent and overlapping temporal commitments to conversion at work in Aneityum.